TLS in Sustainable Mining Engineering: 3D Convergence and Surface Changes in Chamber Excavation in CH Salt Mine “Wieliczka” - Pelagia Gawronek; Andrzej Kwinta; Kamil Sajdak; Piotr Koczwara (Mining)
When volumes of mining excavations change, rock mass is displaced. Convergence in a salt mine may lead to substantial deformations. The displacement may, in turn, cause an inrush of water from the rock mass into the mine, which is a catastrophic event. Hence, salt excavation convergence is regularly monitored. Traditionally, convergence is measured at monitoring stations. The measurements were first performed with rigid instruments (such as a wire extensometer), then with manual laser rangefinders, and now attempts are made to employ terrestrial laser scanning (TLS). This article presents the evolution of TLS surveys in the mine. The method is demonstrated with multiple scans of a heritage chamber at the Wieliczka salt mine. The analyses indicate that TLS streamlines measurements and offers copious results. The main aim of this study was to identify the most effective and reliable determination of geometric changes in the excavation using TLS data from several years. The differences represented by the models adjusted to a common coordinate system with an error of 5 mm can be considered correct and reflecting the actual changes in the excavation. This gives significant opportunities for the use of TLS data in monitoring the behavior of mine workings in the future. However, considering the insufficient accuracy, the technology must not be the sole source of insight into mining excavation convergence.